Weight compensation characteristics of Armeo®Spring exoskeleton: implications for clinical practice and research. Issue 1 (December 2017) - Perry, Bonnie; Evans, Emily; Stokic, Dobrivoje
Abstract Background Armeo®Spring exoskeleton is widely used for upper extremity rehabilitation; however, weight compensation provided by the device appears insufficiently characterized to fully utilize it in clinical and research settings. Methods Weight compensation was quantified by measuring static force in the sagittal plane with a load cell attached to the elbow joint of Armeo®Spring. All upper spring settings were examined in 5° increments at the minimum, maximum, and two intermediate upper and lower module length settings, while keeping the lower spring at minimum. The same measurements were made for minimum upper spring setting and maximum lower spring setting at minimum and maximum module lengths. Weight compensation was plotted against upper module angles, and slope was analyzed for each condition. Results The Armeo®Spring design prompted defining the slack angle and exoskeleton balance angle, which, depending on spring and length settings, divide the operating range into different unloading and loading regions. Higher spring tensions and shorter module lengths provided greater unloading (≤6.32 kg of support). Weight compensation slope decreased faster with shorter length settings (minimum length = −0.082 ± 0.002 kg/°; maximum length = −0.046 ± 0.001 kg/°) independent of spring settings. Conclusions Understanding the impact of different settings on the Armeo®Spring weight compensation should help define best clinical practice and improve fidelity of research.